Uncovering the Potential of Ethnoscience in Science Learning to Improve Students’ Literacy: A Systematic-Literature Review (2014–2024) - Nur Hikmah; Yohandri; Fitri Arsih; Minda Azhar; Abdul Razak (Jurnal Pendidikan IPA Indonesia, 2025)
Literacy is a crucial 21st-century skill aligned with SDG 4 (Quality Education), yet Indonesian students continue to face challenges, as reflected in PISA 2022 results. Ethnoscience, which integrates local wisdom into science education, offers a promising approach to address this issue. This study presents a systematic literature review of research published between 2014 to 2024 on the use of ethnoscience in science learning and its impact on student literacy. The findings indicate that ethnoscience has been widely applied, particularly at the high school level, through strategies such as project-based learning, inquiry, and STEAM. Ethnoscience contributes to improving scientific, environmental, and cultural literacy by contextualizing science learning and fostering engagement, critical thinking, and cultural awareness. This research synthesizes a decade of empirical evidence on ethnoscience integration in science education, maps the strategies employed, and examines their relationship with students’ literacy outcomes. The results suggest that ethnoscience provides a culturally grounded approach that can effectively support the development of science literacy.